Efficiency enhancement of hybrid photovoltaic thermoelectric generator for greenhouse based on temperature distribution - Mohd Ariffin, Mohd Ruzaimi (2024)
Food security is a pressing global issue, prompting the search for sustainable agricultural solutions. Agricultural greenhouses present a viable option by providing controlled environments for crop cultivation. This research focuses on enhancing the efficiency of photovoltaic (PV) systems in greenhouse applications through the integration of thermoelectric generators (TEG). The main goal is to convert residual heat from PV panels into additional electricity using TEGs, thereby optimizing energy utilization. The study tackles critical challenges in greenhouse energy management, such as high energy consumption, excessive solar radiation, and the limitations of conventional PV systems. A hybrid PV-TEG system was developed to capitalize on the temperature difference between the heated surface of solar panels and a controlled cooling mechanism where circulating aquaponic water used as a liquid cooler to enhance power generation. The methodology involved designing a small-scale PV greenhouse system, analyzing the temperature distribution across the PV panels, and developing a power logger for real-time performance monitoring. Feasibility and temperature distribution analyses were conducted through both experimental setups and simulations to optimize the positioning and orientation of TEG modules. In a PV-TEG hybrid system, the temperature distribution significantly affects the performance of both PV panels and TEG modules. Non-uniform temperature distribution can lead to uneven heating, creating "hot spots" that reduce the overall efficiency of the PV panels. Conversely, a uniform temperature distribution helps maintain consistent performance across the panel, minimizing thermal stress and enhancing efficiency and lifespan. Similarly, TEG performance is adversely impacted by non-uniform temperatures, as they generate power based on temperature differentials; cooler areas on the PV panel can lead to suboptimal TEG operation, reducing overall system efficiency. Achieving uniform temperature distribution ensures TEGs are consistently exposed to a reliable heat source, maximizing energy conversion capabilities. To achieve this in this study, the PV panels were installed at an optimal tilt angle of 3° facing South, maximizing solar exposure at average direct normal irradiance of 314.9 W/m2 in Serdang, Malaysia. The hybrid system demonstrated significant energy efficiency improvements, with a 33% reduction in power loss due to temperature mismatches across TEG modules. Strategies employed included selecting the highest performance TEG cell models, implementing controlled thermal management through liquid cooling systems, optimizing TEG placement based on temperature analysis, and designing effective heat sinks. This study also introduces a novel analytical model for PV-TEG integration, the PV-TEG Integrated Module (PV-TEGIM), aimed at optimizing heat distribution and passive cooling techniques. The power output of the PV-TEG hybrid system increased with solar radiation, peaking at 31.05 W at noon. The total electrical energy output of the hybrid system was 31% greater than that of a standalone 100 Wp photovoltaic panel. The findings suggest that this hybrid system can reduce energy consumption in greenhouse applications, lower greenhouse gas emissions, and provide a sustainable energy solution for agricultural production. Future work should focus on expanding the system for larger-scale applications and investigating advanced materials to enhance performance further.